(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2024)
A few years ago, Manuel Alberto Graterón, “Beto”, was a rara avis in the business world. How can one think about the immanence of being or the fall of the Roman Empire while discussing financial investments during an executive session? “It’s a very boring job, very long meetings, monotonous, I didn’t like it”, confesses this Venezuelan engineer, former civil works constructor, structural calculator, passionate about history, philosophy and science, and “writer of esoteric papers”.